Clinical Case of Treating a Child with Functionally Single Ventricle Complicated by the Blood Clot Formation in the Rudimentary Ventricle and Acute Cerebrovascular Accident - M. Barani Lonbani; Y. Segal; V. Dehtiar; О. Romaniuk; A. Grycaiuk; V. Zhovnir (Ukrainian Journal of Cardiovascular Surgery, 2019)
Single ventricle is a congenital heart defect in which there is only one ventricle that may be identified by all anatomical clues. It provides both systemic and pulmonary circulation. If there is another ventricular chamber, it is usually represented only by the outflow tract. Most often, this defect is diagnosed in the first days or months of life. Clinical presentation de-pends on the type of defect, in most cases is characterized by cyanosis after birth. In case of natural course of the disease most patients die in childhood, therefore, they need surgical treatment. Today Fontan procedure allows patients with a single ventricle to survive until adulthood.Objective. To represent a clinical case of treating a patient with single ventricle and analyze the tactics of surgical inter-vention and anticoagulant therapy taking into account blood clot formation in the rudimentary ventricle and acute cerebro-vascular accident caused by it.Materials and methods. The article describes a case of surgical treatment of single ventricle in a child, which was com-plicated by the formation of blood clot in the rudimentary right ventricle causing multiple acute cerebrovascular accidents.Discussion. Anticoagulant therapy does not guarantee freedom from blood clots formation. That is why the use of surgical methods is more reasonable in order to reduce the risk of such complications.Conclusion. Along with the prescription of anticoagulant therapy in patients with single ventricle, special attention should be paid to the surgical modifications of the Fontan procedure with the so-called «blind pouch», which may become a site for the blood clots formation due to the possible stagnation of blood and propensity of such patients to hypercoagulation for a number of reasons.